Systemic Inflammation Impairs Attention and Cognitive Flexibility but Not Associative Learning in Aged Rats: Possible Implications for Delirium - Culley, Deborah J.; Snayd, Mary; Baxter, Mark G.; Xie, Zhongcong; Lee, In Ho; Rudolph, James; Inouye, Sharon K.; Marcantonio, Edward R.; Crosby, Gregory (Frontiers in Aging Neuroscience, 2014)
Delirium is a common and morbid condition in elderly hospitalized patients. Its pathophysiology is poorly understood but inflammation has been implicated based on a clinical association with systemic infection and surgery and preclinical data showing that systemic inflammation adversely affects hippocampus-dependent memory. However, clinical manifestations and imaging studies point to abnormalities not in the hippocampus but in cortical circuits. We therefore tested the hypothesis that systemic inflammation impairs prefrontal cortex function by assessing attention and executive function in aged animals. Aged (24-month-old) Fischer-344 rats received a single intraperitoneal injection of lipopolysaccharide (LPS; 50 ug/kg) or saline and were tested on the attentional shifting task (AST), an index of integrity of the prefrontal cortex, on days 1-3 post-injection. Plasma and frontal cortex concentrations of the cytokine TNFα and the chemokine CCL2 were measured by ELISA in separate groups of identically treated, age-matched rats. LPS selectively impaired reversal learning and attentional shifts without affecting discrimination learning in the AST, indicating a deficit in attention and cognitive flexibility but not learning globally. LPS increased plasma TNFα and CCL2 acutely but this resolved within 24-48 h. TNFα in the frontal cortex did not change whereas CCL2 increased nearly 3-fold 2 h after LPS but normalized by the time behavioral testing started 24 h later. Together, our data indicate that systemic inflammation selectively impairs attention and executive function in aged rodents and that the cognitive deficit is independent of concurrent changes in frontal cortical TNFα and CCL2. Because inattention is a prominent feature of clinical delirium, our data support a role for inflammation in the pathogenesis of this clinical syndrome and suggest this animal model could be useful for studying that relationship further.